2012
DOI: 10.1371/journal.pone.0041892
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Changes in Cell Marker Expression and Cellular Infiltration in a Controlled Cortical Impact Model in Adult Male C57BL/6 Mice

Abstract: BackgroundTraumatic injury to the central nervous system (CNS) triggers a robust inflammatory response that leads to axonal damage and secondary degeneration of spared tissue. In contrast, some immune responses have neuroprotective effects. However, detailed information regarding the dynamics of immune responses after traumatic CNS injury is still unavailable.MethodsIn the present study, changes in the immune cells present in the injured brain, spleen, and cervical lymph nodes (CLNs), which are draining lympha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
174
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 175 publications
(189 citation statements)
references
References 44 publications
15
174
0
Order By: Relevance
“…By differential expression of CD45, the infiltrating MMs (CD45 high /CD11b þ ) have been distinguished from the resident microglia (CD45 low /CD11b þ ). [25][26][27] We found that the CD45 high /CD11b þ population was absent in the naive brain (data not shown) and the contralateral hemisphere, but appears in the ipsilateral hemisphere ( Figure 4B). The MM (CD45 high /CD11b þ ) population was subjected to the analysis post ischemia.…”
Section: Ly-6cmentioning
confidence: 75%
“…By differential expression of CD45, the infiltrating MMs (CD45 high /CD11b þ ) have been distinguished from the resident microglia (CD45 low /CD11b þ ). [25][26][27] We found that the CD45 high /CD11b þ population was absent in the naive brain (data not shown) and the contralateral hemisphere, but appears in the ipsilateral hemisphere ( Figure 4B). The MM (CD45 high /CD11b þ ) population was subjected to the analysis post ischemia.…”
Section: Ly-6cmentioning
confidence: 75%
“…These data support other studies that evaluated macrophage and immune cell infiltration dynamics in TBI models. 30,31 Due to technical limitations when combining internalization staining protocols for M1-/M2-like markers with CD11b/CD45 cell surface markers, it was not possible to determine whether the infiltrating macrophages after were more M1-or M2-like polarized, but the peak in infiltration corresponded with high expression levels of both M1-and M2-like protein markers in this study.…”
Section: Fig 7 (Continued)mentioning
confidence: 90%
“…This staining protocol was reported previously as a reproducible method for the identification of macrophage populations; however, it does not exclude some subpopulations of dendritic cells (97,98). Intraperitoneal injection of P. gingivalis (HK-W50) induced a similar M1/M2 macrophage ratio in the peritoneal cavity as that found in gingival tissue.…”
Section: Figurementioning
confidence: 99%